CHALLENGES AND PROSPECTS OF NORTHWARD RELOCATION AND ADAPTATION OF STONE FRUIT CROPS TO THE FOREST-STEPPE AND POLISSIA ZONES UNDER CLIMATE CHANGE CONDITIONS - Pechko В.; Hrynyk Р. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
Over the past decades, the planet's climate has undergone significant changes, primarily attributed to greenhouse gas emissions. Consequently, there is an increasing need to develop adaptation tools across various sectors of human activity, including agriculture, particularly in the production of perennial crops. This article presents an analysis of the impact of climate change on the cultivation of stone fruit crops across different agro-climatic zones, with examples drawn from research conducted by domestic scientific institutions. A comparative assessment of weather conditions in the Polissia, Forest-Steppe, and Steppe zones of Ukraine was performed for the periods 1930–1956 and 2006–2022. It was established that the greatest increase in the mean annual air temperature was recorded in the Polissia region, rising by 2.3 °C. Based on the research findings, the authors conclude that climate change in Ukraine, driven by global warming, is causing significant shifts in weather patterns. These changes have both positive and negative implications: on one hand, they create favorable conditions for the cultivation of cherry, plum, and sweet cherry in the Polissia zone; on the other hand, they reduce plant resilience, promote premature flowering, and increase susceptibility to diseases and pest damage, thus necessitating the adaptation of agricultural practices to mitigate negative impacts on orchard management. It should also be noted that the cultivation of thermophilic fruit species in the Forest-Steppe and Polissia zones requires particular attention to plant protection against winter damage. Therefore, the placement of industrial stone fruit plantations in the Forest-Steppe and Steppe zones of Ukraine should be based on the specific features of climate change in these regions, taking into account regional characteristics and agro-climatic factors while applying adaptive technologies for fruit production.